Design of a T-S Fuzzy Regulator Using PDC and NAE Approach and Integral-Optimal Sliding Mode Control for Current-Controlled Electromagnetic Levitation System - Pandey, Amit; Adhyaru, Dipak M. (2023 3rd International Conference on Emerging Frontiers in Electrical and Electronic Technologies (ICEFEET), 2023)
In this article, the Takagi-Sugeno (T-S) regulators and integral sliding mode with optimal control-based controllers are proposed for the current-controlled electromagnetic levitation system (CC-EMLS). The Takagi-Sugeno regulator is designed using the parallel distributed compensator (PDC) and negative absolute eigenvalue (NAE) for achieving the set-point of the levitating steel ball. The Takagi-Sugeno regulator is not suitable for systems with significant uncertainties and cannot handle large-scale models because in the process of gain calculation it requires many linear models. A sliding mode controller (SMC) is therefore developed to deal with the uncertainties in the system model. The chattering effect is observed in the sliding mode control technique. The integral sliding mode control (ISM) provides the chatter-free control input that protects the system from becoming unstable, and optimal control in the ISMC provides the necessary action for tracking the desired position. The effectiveness of the proposed control techniques is compared by adding the disturbance to the levitating object mass. The designed controllers are robust enough to cater to external disturbances and parameter variations. The transient and steady-state performances of the system are analyzed for the designed controllers in terms of integral errors such as ISE, IAE, ITSE, and ITAE. Simulation experiments presented in the article validate the performance claim and robustness of the proposed controller for the magnetic levitation system.